Computed tomography and cross-sectional anatomy of the head in the giant anteater (Myrmecophaga tridactyla) - Farha, Aline Herrera [UNESP]; da Silva, Jeana Pereira [UNESP]; Bete, Stela Bonadia de Souza [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Schimming, Bruno Cesar [UNESP] (Wiley, 2021)
The aim of this study was to identify the anatomical structures in the head region of the giant anteater (Myrmecophaga tridactyla) using computed tomography. For this, three giant anteater corpses, adult and female, were used. The tomographic analysis was performed in sequential order in rostrocaudal direction. Subsequently, the heads of these animals were sectioned in cross sections of approximately 1.5 cm each. Tomographic images were compared with anatomical sections. The association between computed tomography and anatomical sections allowed the visualization of anatomical structures found in the nasal, oral, cranial, pharyngeal and ear cavities. An elongated oral cavity delimited by the elongated mandible was observed. The oral cavity was mainly occupied by a thin and elongated tongue formed mainly by the union of the sternoglossal muscles. The nasopharynx and oropharynx extended up to the neck at the level of the fifth cervical vertebra. The findings of this study suggest that the giant anteater has a head with structures morphologically adapted to its feeding habits, such as an elongated skull, tongue, styloid bones and mandible. In addition, based on the results of this study, it is possible to suggest that computed tomography is a pivotal tool for the veterinary routine of wild animals, since it allowed the identification of anatomical structures found in the head of the giant anteater.
Keywords: head; imaging diagnostic; myrmecophages; wildlife; Xenarthra